Application of chemometric approach for QbD-Enabled development and validation of an RP-HPLC method for estimation of methotrexate. Issue 15 (2nd October 2019) - Jain, Atul; Beg, Sarwar; Saini, Sumant; Sharma, Teenu; Katare, O. P.; Singh, Bhupinder
Abstract: The present work describes Quality by design (QbD)-oriented development of a reverse phase high performance liquid chromatographic (RP-HPLC) method for quantification of methotrexate (MTX). Initially, for performing HPLC studies with UV detector, an appropriate wavelength was selected using a novel technique of Principal Component Analysis (PCA). Risk assessment study was performed, followed by factor screening study using a fractional factorial design (FFD). Subsequently, factor optimization was conducted using a central composite design (CCD), with flow rate and mobile phase ratio as the critical method parameters (CMPs), and tailing factor (TF), theoretical plate count (TPC) and % assay selected as the critical analytical attributes (CAAs). Polynomial modeling was performed to embark upon an optimal solution, followed by numerical and graphical optimization. Chromatographic separation was conducted using the mobile phase composition of acetonitrile (ACN) and ammonium acetate buffer (10 mM, pH 6) in the ratio of 25:75 v/v, flow rate of 0.8 mL/min, column oven temperature of 40 °C, and UV detection at 257 nm. Further, the analytical method was validated as per ICH Q2(R1) guidelines for linearity, accuracy, precision, sensitivity and robustness, ratifying that all the parameters were within the acceptable limits for quantification of MTX. GRAPHICAL ABSTRACT: